Cathepsin S as a potential therapeutic target for chronic pain - Karli Montague-Cardoso; Marzia Malcangio (Elsevier, 2020)
Chronic pain is a distressing yet poorly-treated condition that can arise as a result of diseases and injuries to the nervous system. The development of more efficacious therapies for chronic pain is essential and requires advances in our understanding of its underlying mechanisms. Clinical and preclinical evidence has demonstrated that immune responses play a crucial role in chronic pain. The lysosomal cysteine protease cathepsin S (CatS) plays a key role in such immune response. Here we discuss the preclinical evidence for the mechanistic importance of extracellular CatS in chronic pain focussing on studies utilising drugs and other pharmacological tools that target CatS activity. We also consider the use of CatS inhibitors as potential novel antihyperalgesics, highlighting that the route and timing of delivery would need to be tailored to the initial cause of pain in order to ensure the most effective use of such drugs.